The Correlation Between Humidity, Temperature, and Noise With Sleep Quality at Intensive Care Unit (ICU) - Sri Suparti; Jebul Suroso (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Temperature, humidity, and noise are factors that affect sleep quality. The objective of the research is to determine the effect of humidity, temperature, and room noise on sleep quality of (Intensive Care Unit) ICU patients. Methods: A quantitative research with the cross-sectional approach, involving 84 patients taken by consecutive sampling, with the inclusion criteria of at least having already spent more than two days in ICU, having age between 20-70 years, and being conscious and cooperative. The patients were observed using observation sheets and The Richards-Campbell Sleep Questionnaire (RCSQ). A thermohygrometer and sound level meter for noise recording were used to measure the temperature and humidity. Simple linear regression was used to analyze the data. Results: It was found out that the average sleep quality of patients in the intensive room was 28.51, which categorized as poor sleep quality; the mean humidity in ICU was 56.98; the room temperature was 26.40, and the noise was 66.01. The noise level at the ICU significantly affected the patients’ sleep quality (p-value = 0.020 <0.05), while temperature and humidity did not influence the patients' sleep quality. Conclusion: Most of the respondents had a poor quality of sleep. Controlling the conversation and activities among staff, using earplugs, and modifying the alarm can be done to reduce the noise at the ICU to enhance the quality of sleep of the patients.